Global Learning for Health Equity: A Literature Review. Issue 1 (17th October 2022) - Ogbolu, Yolanda; Dudding, Ruth; Fiori, Kevin; North-Kabore, Janette; Parke, Dana; Plum, Rev. Alexander; Shin, Sonya; Rowthorn, Virginia
Background: In high income countries struggling with escalating health care costs and persistent lack of equity, there is growing interest in searching for innovative solutions developed outside national borders, particularly in low- and middle-income countries (LMICs). Engaging with global ideas to apply them to local health equity challenges is becoming increasingly recognized as an approach to shift the health equity landscape in the United States (US) in a significant way. No single name or set of practices yet defines the process of identifying LMIC interventions for adaptation; implementing interventions in high-income countries (HIC) settings; or evaluating the implementation of such projects. Objectives: This paper presents a review of the literature describing the practice of adapting global ideas for use in the US, particularly in the area of health equity. Specifically, the authors sought to examine; (i) the literature that advocates for, or describes, adaption of health-related innovations from LMICs to HICs, both generally and for health equity specifically, and (ii) implementation practices, strategies, and evidence-based outcomes in this field, generally and in the area of health equity specifically. The authors also propose terminology and a definition to describe the practice. Methods: The literature search included two main concepts: global learning and health equity (using these and related terms). The search consisted of text-words and database-specific terminology (e.g., MeSH, Emtree) using PubMed, Embase (Elsevier), CINAHL (Ebsco), and Scopus in March 2021. The authors also contacted relevant experts to identify grey literature. Identified sources were categorized according to theme to facilitate analysis. In addition, five key interviews with experts engaged with global ideas to promote health equity in the United States were conducted to develop additional data. Results: The literature review yielded over ninety (n = 92) sources relating to the adaptation of global ideas from low resource to higher resource settings to promote health equity (and related concepts). Identified sources range from those providing general commentaries about the value of seeking health-related innovations outside the US border to sources describing global projects implemented in the US, most without implementation or outcome measures. Other identified sources provide frameworks or guidance to help identify and/or implement global ideas in the US, and some describe the role of the World Health Organization and other international consortia in promoting a global approach to solving domestic health equity and related challenges. Conclusions: The literature review demonstrates that there are resources and commentary describing potential benefits of identifying and adapting novel global ideas to address health equity in the US, but there is a dearth of implementation and evaluation data. Terminology is required to define and frame the field. Additional research, particularly in the area of implementation science and evidence-based frameworks to support the practice of what we define as 'global learning' for health equity, is necessary to advance the practice.